Ahammiyah al-Balagah al-’Arabiyah fi tafsir al-Qur’an - Ahmad Syatibi (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2016)
The Qur’an was revealed in Arabic. This holy book has two main objectives: as God’s miracle and as an evidence of the prophethood of His last messenger, Muhammad. As a miracle, all of the Qur’anic verses are God’s guidance. The guidance and miracle of the Qur’an is traceable in its balaghoh (rhetoric). Understanding this rhetoric will guide people to know about what to do or not to do according to this book. To learn the Qur’an as guidance from its rhetoric, people are to live on their lives according to the Qur’anic teachings. The balaghoh is a foundation to grasp and reveal the meaning of the Qur’an.DOI: 10.15408/insaniyat.v1i1.4509